The Numeracy Ability of Field Dependent Students in Solving Well Structured Problems - Maharani Izzatin; Kartono Kartono; Zaenuri Zaenuri; NR Dewi (Universitas Negeri Semarang, 2022)
Abstract. Numeracy is an individual's ability to formulate, identify, understand and implement the basics of mathematics in various contexts that individuals need in everyday life. numeracy is closely related to solving mathematical problems. The problems experienced by students with field dependent cognitive style are still low mathematical problem solving abilities. The purpose of this study was to describe the student’s numeracy skills with field dependent cognitive style in solving well-structured problems. This research is a qualitative research with the researcher as the main instrument. The supporting instruments are the Group Embeded Figure Test (GEFT), numeracy test, and interview guide. The results showed that students with field dependent cognitive style had good numeracy skills in the aspect of counting and numeracy relations. However, students' numeracy skills in the aspect of arithmetic operations still need to be improved.